Need Analysis of Non-English Major Students in Learning English at the Management Programme Universitas Muhammadiyah Makassar - Sri Dewi Fortuna; Siti Asriati; Hilda Hafid (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this study was to identify the problems and needs of students studying English at the Management Universitas Muhammadiyah Makassar. A descriptive qualitative design was used in this study. The target audience for this survey is students in management programs. Ten participants were enrolled in this study. Samples were collected using a direct sampling technique. Researchers collected data using interviews and documents. Research has shown that the problems students face in learning English in management programs are lack of vocabulary and difficulty in pronouncing words in English. Students also need knowledge to increase their vocabulary and understanding of English grammar so that they can speak fluently for future work. We need more interesting, understandable and relevant speaking skills and materials